Differential Harnack Estimates for a Semilinear Parabolic System. (10th March 2019) - Wu, Hui
Abstract : In this paper, we prove differential Harnack inequalities for positive solutions of a semilinear parabolic system on hyperbolic space. We use the inequalities to construct classical Harnack estimates by integrating along space-time.